2019
DOI: 10.1371/journal.pone.0224974
|View full text |Cite
|
Sign up to set email alerts
|

Distinct varieties of aesthetic chills in response to multimedia

Abstract: The experience of aesthetic chills, often defined as a subjective response accompanied by goosebumps, shivers and tingling sensations, is a phenomenon often utilized to indicate moments of peak pleasure and emotional arousal in psychological research. However, little is currently understood about how to conceptualize the experience, particularly in terms of whether chills are general markers of intense pleasure and emotion, or instead a collection of distinct phenomenological experiences. To address this, a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 84 publications
3
69
0
Order By: Relevance
“…This cognitive state should result in the inhibition of the motor component of the response to beautiful stimuli. This hypothesis is supported by behavioural research investigating the elicitation of chills by beautiful stimuli, showing that participants experience a strong relaxation during the chill episode (Bannister, 2019;Schoeller & Perlovsky, 2016). Moreover, recent neuroimaging results support the presence of motor inhibition during aesthetic experiences (relevant research related to the present hypothesis is reported in Table 1, second section; brain areas involved in this mechanism are presented in Figure 1B).…”
Section: Contemplation Of Beauty and Motor Inhibitionsupporting
confidence: 79%
See 1 more Smart Citation
“…This cognitive state should result in the inhibition of the motor component of the response to beautiful stimuli. This hypothesis is supported by behavioural research investigating the elicitation of chills by beautiful stimuli, showing that participants experience a strong relaxation during the chill episode (Bannister, 2019;Schoeller & Perlovsky, 2016). Moreover, recent neuroimaging results support the presence of motor inhibition during aesthetic experiences (relevant research related to the present hypothesis is reported in Table 1, second section; brain areas involved in this mechanism are presented in Figure 1B).…”
Section: Contemplation Of Beauty and Motor Inhibitionsupporting
confidence: 79%
“…Preliminary results in empirical aesthetics research already support this intuition. Indeed, aesthetic chills have been considered as a universal marker of openness to experience (McCrae, 2007;Silvia and Nusbaum, 2011), enhance altruism (Fukui and Toyoshima, 2014) and might be triggered by mechanisms such as shared experience and empathic resonance (Bannister, 2019;Schoeller et al, 2018), which reduce the uncertainty regarding other people's contents of mind (Schoeller et al, 2018). In simple terms, within a relational context, the experience of beauty might favour a deeper understanding of others' mind (Pelowski et al, 2018;Schoeller et al, 2018) through the emotional resonance (Fuchs and Koch, 2014;Gallese, 2007) between minds.…”
Section: Possible Future Applicationsmentioning
confidence: 99%
“…We assume that piloerection in response to kama muta reflects a social signal and represents a motivation to approach others (Maruskin et al., 2012; Zickfeld, Schubert, Seibt, Blomster, et al, 2019). Maruskin and colleagues provided some first evidence for this notion, showing that a specific form of chills, so‐called goosetingles , is related to approach motivations (see also Bannister, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As is the case with sophisticated music, intense music is linked with openness to experience (Schäfer & Mehlhorn, 2017), a known personality correlate of chills. Interestingly, these results provide some support for the possibility that different types of chills are elicited by different types of feelings and affective states expressed or evoked by music (Bannister, 2019;Maruskin et al, 2012).…”
Section: Resultsmentioning
confidence: 60%
“…Conflicting effects of valence on chills have been discussed in the context of being moved, a mixed emotional state involving sadness and joy (Menninghaus et al, 2015). More specifically, being moved has been associated with chills when listening to music (Bannister, 2019(Bannister, , 2020Bannister & Eerola, 2018;Benedek & Kaernbach, 2011), and has been found to mediate the relationship between liking and sadness in response to music (Vuoskoski & Eerola, 2017). Moving stimuli often feature narrative displays of social separation or reunion (Wassiliwizky et al, 2015), prosocial behaviour (Wassiliwizky et al, 2017), or self-sacrifice (Konečni et al, 2007), but it remains unclear how such narrative features translate to music, and how stimulus valence relates to the occurrence of chills.…”
Section: Introductionmentioning
confidence: 99%